Effect of Electroacupuncture at Zusanli (ST36) on Intestinal Microbiota in Rats With Chronic Atrophic Gastritis - Huang, Wanyi; Yau, Yuenming; Zhu, Jingru; Wang, Yingjie; Dai, Zhipeng; Gan, Huijuan; Qian, Linchao; Yang, Zongbao (Frontiers in Genetics, 2022)
Background: Electroacupuncture, a common treatment for Chronic Atrophic Gastritis (CAG) in China. We aimed to determine the effect of electroacupuncture at Zusanli on intestinal microbiota in CAG rats. Methods: 42 SD rats were randomly divided into normal group (NC group, 10 rats), and model group (MG group, 32 rats). Rats in MG group were established as CAG disease models. After that, the rats in MG group were randomly divided into Chronic Atrophic Gastritis group (CAG group,10 rats), Electroacupuncture group (EA group,10 rats) and Vitacoenzyme group (Vit group, 10 mice). Rats in NC group and CAG group were carried out a 30 min/d confinement for 4 weeks. Rats in EA group were carried out electroacupuncture at Zusanli (ST36) 30 min/d for 4 weeks. Rats in Vit group were given Vitacoenzyme solution 10ml/(kg·d) for 4 weeks. Histopathological changes in the gastric mucosa was observed by hematoxylin and eosin staining, and the gene expression level of p53, Bcl-2 and c-myc was tested in qPCR method. 16S rDNA sequencing technique to detect structural changes and relative abundance expression of intestinal flora. Result: Compared with NC group, the gastric mucosal pathology in CAG group was significantly inflammatory infiltration, and the gastric mucosal lesions in electroacupuncture group were improved remarkably; the expression of p53 and c-myc genes in CAG group was increased (P<0.05), while the expression of Bcl-2 genes was decreased (P<0.05), in EA group, the expression of p53 and c-myc genes decreased (P<0.05), while the expression of Bcl-2 gene increased (P<0.05); the abundance of bacteria such as Lactobacillus, Desulfobacterota and Bacteroides_pectinophilus_group in CAG group increased (P<0.05), while the abundance of bacteria such as Gastranaerophilales, Romboutsia and Blautia decreased (P<0.05), and the relative abundance of Desulfobacterota and Helicobacter in EA group was decreased (P<0.05), while the relative abundance of probiotic bacteria such as Oscillospirales, Romboutsia, Christensenellaceae increased (P<0.05). Conclusion: Electroacupuncture at Zusanli can promote the repair of pathological damage to the gastric mucosa in rats with CAG, and the mechanism might relate to reducing the relative abundance of harmful bacteria, increasing the relative abundance of intestinal probiotics, and regulating the intestinal microbiota.